2019
DOI: 10.1002/aenm.201802928
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene‐Based In Situ Doping of N and Fe into a 3D Cross‐Like Hierarchical Carbon Composite for High‐Performance Supercapacitors

Abstract: Fullerene-based carbons are promising electrode materials for supercapacitors due to their unique carbon structures and tunable architectures at the molecular level. By introducing various functional groups with many elements on the fullerene cages, diverse in situ metal/non-metal-doped carbon materials with enhanced pseudocapacitances and/or double layer capacitances can be prepared. In the present work, a fullerene derivative, ferrocenylpyrrolidine C60, containing nitrogen and iron, was chosen as the only pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 69 publications
1
48
0
Order By: Relevance
“…The ESR resistances of PVPA/Ni1, PVPA/Ni3, PVPA/Ni5, and PVPA/Ni10 device electrodes were obtained as 0.31, 0.59, 1.31, and 2.40 Ω, respectively. The Warburg resistance (W) of the system indicates the ion diffusion through the pores on the electrode surface in the low frequency region . The W of all devices demonstrates that the AC‐PVPA/Ni system generates high CD performance by allowing maximum ion diffusion at the electrode level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESR resistances of PVPA/Ni1, PVPA/Ni3, PVPA/Ni5, and PVPA/Ni10 device electrodes were obtained as 0.31, 0.59, 1.31, and 2.40 Ω, respectively. The Warburg resistance (W) of the system indicates the ion diffusion through the pores on the electrode surface in the low frequency region . The W of all devices demonstrates that the AC‐PVPA/Ni system generates high CD performance by allowing maximum ion diffusion at the electrode level.…”
Section: Resultsmentioning
confidence: 99%
“…The energy density is indicated by E , the power density by P , the voltage window by Δ V and the discharge time Δ t …”
Section: Methodsmentioning
confidence: 99%
“…The resistances of the supercapacitors bearing BG(Atri) 2 , BG(Atri) 2 /0.1IL, BG(Atri) 2 /H 3 PO 4 /0.1IL, BG(Imi) 2, BG(Imi) 2 /0.1IL, and BG(Imi) 2 /H 3 PO 4 /0.1IL were found to be 4.31, 2.25, 1.21, 2.65, 1.81, and 0.95 Ω, respectively. The ion diffusions throughout the pores in the surface of the electrodes are represented by the Warburg resistance of the system at the low‐frequency area . The Warburg impedance results revealed that the activated carbon and BG(Atri) 2 /H 3 PO 4 /0.1IL and BG(Imi) 2 /H 3 PO 4 /0.1IL systems provide enhanced ion diffusions on the electrode surfaces, improving the charge‐discharge performances of the systems.…”
Section: Resultsmentioning
confidence: 99%
“…The produced supercapacitors were evaluated for their energy capacity and power densities by utilization of Equations , correspondingly. E=1/2×Cnormals×()italic∆V2/3.6, P=E×()3600/italic∆t, where E is the energy density, Δ V is the voltage window, and P is the power density …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation